An introduction to physical science - Shipman, James T. (Brooks/Cole, Cengage Learning, 2013)
An Introduction to Physical Science presents a survey of the physical sciences--physics, chemistry, astronomy, meteorology, and geology--for non-science majors. Topics are treated both descriptively and quantitatively, providing flexibility for instructors who wish to emphasize a highly descriptive approach, a highly quantitative approach, or anything in between